Determinants of firm’s value: Evidence from financial industry - Endri Endri; Moch Fathony (Management Science Letters, 2020)
The purpose of this study was to estimate and analyze the effect of dividend policy, profitabil-ity, firm size, leverage, and growth on firm value in financial sector listed on Indonesia Stock Exchange from 2013 to 2017. A quantitative method is used for this research with 21 companies as research object, measured by purposive sampling techniques. The data analysis method used is panel data regression. The results show that firm size, leverage, and growth did not have any significant effect on firm value in financial sector companies in the period 2013-2017. However, dividend policy and profitability proved to have significant positive effects on firm value in financial sector companies for the period 2013-2017. Simultaneous results also show that dividend policy, profitability, firm size, leverage and growth had some effects on firm value.